Effect of MgO on characterizations and mechanical properties of red soil as oxygen carrier in chemical looping combustion - Selvarajoo K.; Afandi N.F.; Manap A.; Zainuddin R.A.; Mahalingam S.; Kadir N.F. (Institute of Physics Publishing, 2023)
Crystallite size; Field emission microscopes; Magnesia; Mechanical properties; Morphology; Nanostructured materials; Oxygen; Scanning electron microscopy; Waste incineration; Waste treatment; Wastewater treatment; Water treatment; Brunauer emmett tellers; Building blockes; Chemical-looping combustion; Field emission scanning electron microscopy; High surface area; Oxygen Carrier; Phase analysis; Supported materials; Soils